Finite-time boundary stabilization of the reaction-diffusion system with switching time-delay input. (January 2022) - Ghaderi, Najmeh; Keyanpour, Mohammad; Mojallali, Hamed
The paper is devoted to the study of boundary finite-time control for a reaction-diffusion (RD) system with switching time-delayed input. The RD system with switching time-delay input is converted to a switching system of RD equation cascaded with a transport equation with non-delay boundary input. Next, a novel switching controller is designed for the cascaded RD-transport system based on the backstepping technique, and this causes the closed-loop system to be convergence in a finite-time. Simulation results are provided to exhibit the effectiveness of the proposed method.